Dördüncü Bürde karşılaştırmalı bir edebi çalışma - Alsakka, Naim (My University, 2024)
Bu çalışmada, Hz. Peygamber'i -Allah'ın salatı ve selamı onun üzerine olsun-öven, iki yüz beyitten oluşan İmam el-Bûsirî ve çağının şairlerinin prensi olarak nitelendirilen Ahmed Şevki gibi önceki şairlerin Bürde kasidelerinden aşağıda kalmayan bir kaside incelenecektir. Bu tezimizde Peygamber -sallallahu aleyhi ve sellem- döneminden günümüze kadar Kaside-i Bürde tarzında nazmedilmiş en önemli şiirleri kronolojik olarak takip edecek, çağdaş bir şairin hayal gücünden yeni manaları tanıyacağız. Eleştirmenlerin ifadelerine göre, yeteneği ve şiirsel hayal gücü ile önceki dönemlerin birçok şairini geçen söz konusu şair Temim el-Berğûsî, akranları arasında önemli ve itibar sahibi bir şair olarak kabul edilmektedir. Şair el-Berğûsî'nin, el-Bûsirî ve Ahmed Şevki'nin Bürde kasidelerine nazire olarak yazdığı bu kaside, aralarındaki ortak anlamlar ve sanatsal imgelerle bu alanlarda getirdiği yenilikler üzerinden bir araştırma yapılacaktır. Tezin sonunda el-Berğûsî'nin Bürde'si ile İmam el-Bûsirî'nin ve Ahmed Şevki'nin Bürdeleri arasında yapılan mukayesenin sonuçları değerlendirilecektir.

In this study, a poem composed of two hundred verses in praise of the Prophet - may God’s prayers and peace be upon him - will be studied and is no less important than the previous Al-Burdah poems, which were composed by poets of their eras such as Imam Al-Busairi, and the prince of poets of his time, Ahmed Shawqi. We will come to the chronological progression in the poems of al-Burdah from the era of the Prophet - may God bless him and grant him peace - to our present time. In this thesis, we will learn about new meanings that came from the imagination of a contemporary poet. However, according to the testimony of critics, in his talent and poetic imagination, he preceded many poets of previous eras; Tamim Al-Barghouti was considered a glorified poet of great importance and standing among his peers among the poets. There will also be a study of an important axis, which is the opposition of the poet Al-Barghouti to the poems of Al-Busairi and Ahmed Shawqi in terms of the meanings and the common artistic images and what he added to them. At the end of the thesis, some balances will be made between Al-Barghouti's Burdah and the two poems Al-Burdah by Imam Al-Busairi and Ahmed Shawqi in terms of images and meanings.
Keywords: Arabic literature; Arap Edebiyatı; Edebiyat -Şiir - Bürde - Büsiri Poem - Litriture - Busiri; Kaside of Burde; Kaside-i Bürde; Ode of Burde; Poetry; Şiir; أدبيات عربية; شرح قصيدة البردة; شعر